Peran Sistem Informasi Akuntansi dan Kompetensi SDM Dalam Meningkatkan Kualitas Pelaporan Keuangan Dengan Penerapan SAK EMKM Pada UMKM Kabupaten Bandung - Arifa, Noviana Nur; Alamsyah, Muhammad Iqbal (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
This study aims to determine the role of Accounting Information Systems and HR Competence in Enhancing Financial Reporting Quality with the Implementation of SAK EMKM on MSME Kabupaten Bandung. The approach used in this research is quantitative. The population in this study was 17,757 MSMEs. This study uses nonprobability sampling, especially purposive sampling. The sample in this study was 100 respondents who were analyzed using SmartPLS 4.0 software. The results show that the accounting information system has no significant effect on the financial reporting quality, the accounting information system has a significant effect on the implementation of SAK EMKM, HR competence has a significant effect on the financial reporting quality, and HR competence has a significant effect on the implementation of SAK EMKM. In addition, the results of the study show that the accounting information system and HR competence have a significant effect on the financial reporting quality which is mediated by the implementation of SAK EMKM.